Potensi Aktivitas Antibakteri Kombucha Kulit Batang Faloak (Sterculia quadrifida R.Br.) dari Pulau Timor - Lalong, Paulus R F; Laynurak, Yoseph M; Taek, Maximus M (Universitas Pattimura, 2023)
Exploration of the potential of alternative ingredients to replace black tea or green tea in making kombucha has begun to be widely carried out. On Timor Island, faloak stem bark is processed into a traditional drink by some locals. For this reason, the use of faloak stem bark as a basic ingredient for kombucha needs to be studied, especially in exploring its antibacterial potential, which is analyzed based on the concentration of sugar used. This study aims to determine the chemical characteristics and antibacterial activity of faloak stem bark kombucha with various concentrations of sugar. The methods involved making faloak stem bark kombucha with varying sugar concentrations of 6, 8, 10, and 12% (w/v), and testing chemical characteristics in the form of pH, total acid, total sugar, and total phenol tests. Meanwhile, the antibacterial activity testing used a good diffusion method against Escherichia coli ATCC 25922 bacteria. After 14 days of fermentation, faloak stem bark kombucha with a 12% sugar concentration showed the best chemical characteristics, with pH, total acid, total sugar, and total phenol values of 2.91, 1.19%, 7.33%, and 420.15 mg GAE/L, respectively. Furthermore, antibacterial activity also showed the highest inhibition (13.02 mm) at a sugar concentration of 12%. Thus, faloak bark kombucha made with a sugar concentration of 12% has the potential to be antibacterial.